The formation of microorganism communities in the soil under the effect of chitosan and runner bean (Phaseolus coccineus L.) cultivation - Danuta Pięta (Acta Agrobotanica, 2013)
The subject of the studies was the soil with introduced solutions containing 0,1% chitosan. These materials were obtained from the Institute of Chemical Fibres in L6d2 (in the form of a microcrystalline gel) and also from the Department of Food Biochemistry and Chemistry of the University of Agriculture in Lublin (in a liquid form,i.e.dissolved in acetic acid). In order to set an experiment in a growth chamber, grey brown podzolic soil formed from loesses and taken from a mechanically treated belt of black fallow was used. The soil (1000 g) was watered every 8 days with 100 ml of examined chitosan solutions per pot. Control soil was watered with sterile distilled water. Seven days after each watering, soil samples were taken for microbiological analysis. Then 25 runner bean seeds were sown into each pot. After six weeks of plants' growth the experiment was finished and the number of plants was counted, their healthiness determined and soil microbiological analysis was performed. Regardless of chitosan form introduced to the soil it stimulated the growth of bacteria and fungi, since in these experimental combinations was found a significantly higher number of microorganisms as compared with the control. A particular high increase in the number of microorganism colonies was observed with simultaneous growth of plants and the application of chitosan. A considerable increase of fungi colonies from the Trichoderma genus was found in the soil treated with chitosan in the form ofboth a microcrystalline gel and a liquid. The species of this genus are considered to be antagonists; it affects pathogenic fungi through competition, antibiosis and over-parasitism. An increase in colonies of saprophytic microorganisms, including antagonistic ones of Bacillus spp. and Pseudomonas spp. was observed in the soil treated with chitosan . On the other hand, in the soil after the growth of bean and treated watered with chitosan only few colonies of Fusarium oxysporum f.sp. phaseoli- bean pathogen were found. The healthiness of plants grown in soil treated with chitosan was significantly better as compared to the control. The populations of antagonistic microorganisms formed in the soil in these treatments probably limited the growth of pathogenic fungus.